Antacid Therapy and Disease Progression in Patients with Idiopathic Pulmonary Fibrosis Who Received Pirfenidone - Kreuter, Michael (Respiration, 2017)
BACKGROUND: Gastroesophageal reflux disease is a potential risk factor for idiopathic pulmonary fibrosis (IPF) progression; however, the impact of antacid therapy (AAT) is under debate. OBJECTIVE: To evaluate the effect of AAT on IPF progression in pirfenidone-treated patients. METHODS: This post hoc analysis included patients with IPF who received pirfenidone in 3 trials (CAPACITY [PIPF-004/PIPF-006] and ASCEND [PIPF-016]). Pulmonary function, exercise tolerance, survival, hospitalizations, and adverse events (AEs) over 52 weeks were analyzed by baseline AAT use. Disease progression was defined as a decrease in forced vital capacity (FVC) of ≥10%, a decrease in 6-min walking distance of ≥50 m, or death over 1 year. RESULTS: Of 623 patients, 44% received AAT. No significant differences were found at 52 weeks (AAT versus non-AAT, respectively) in disease progression (24.9 vs. 30.6%; p = 0.12), all-cause mortality rate (2.9 vs. 4.0%; p = 0.47), IPF-related mortality rate (1.1 vs. 2.0%; p = 0.37), all-cause hospitalization rate (16.1 vs. 18.3%; p = 0.48), or mean change in percent FVC (−2.7 vs. −3.1%; p = 0.44). A relative, but not absolute, FVC decline of ≥10% favored AAT (15 vs. 22%; p = 0.03). Severe gastrointestinal AEs (3.7 vs. 0.9%; p = 0.015) and severe pulmonary infections (3.7 vs. 1.1%; p = 0.035) were more frequent with AAT. CONCLUSIONS: AAT and pirfenidone had outcomes comparable to those of pirfenidone alone in patients with IPF, underscoring the need for prospective trials to elucidate the role of AAT with or without antifibrotic drugs as a treatment for IPF.